Artificial intelligence in oncology: promise, peril, and the future of patient–physician interaction - Thind, Birpartap S.; Tsao, Che-Kai (Frontiers in Digital Health, 2025)
Artificial intelligence (AI) is increasingly embedded in oncology. While initial technical evaluations emphasize diagnostic accuracy and efficiency, the impact on patient–physician interaction (PPI)—the foundation of trust, communication, comprehension, and shared decision-making—remains underexplored. In this review, we studied the current development of AI technology facing both physicians and patients with a focus in cancer care. Among different AI technologies, chatbots, large language model agents, and extended reality applications have shown the promise to date. Survey data suggest oncologists recognize AI's potential to augment efficiency but remain cautious about liability and the erosion of relational care. Key to future AI success in improving cancer care critically depends on design, validation, governance, and human guidance and gatekeeping in care delivery.